Grammatologic Intertextuality in the Narrative of Spanish Writers (XXI Century. Spanish Literature and Culture, 2004)
Coming from the claim that ‘language, above all, is writing’, grammatology is developed: astrategy focalized in a theoretical approximation that will mollify the prejudices of Western thought thatundervalue writing. In this study, we see carried out an enormous labor of comparison and approximationof the different ways to highlight individuality which is characteristic of these authors who, interestingly,resemble each other.
Keywords: grammatology; Spanish; Spanish writers; comparison